Kadar Lemak Tubuh Pemain Bola Basket SMA Negeri 3 Kabupaten Ciamis (Berdasarkan Posisi Pemain) - Rahmatulloh, M. Tapan; Rustiawan, Hendra; Rohendi, Andang; Hartono, Tony (Jurnal Keolahragaan, 2023)
This study aims to determine how much body fat percentage in male and female students of the Ciamis Regency Public High School 3 basketball team. To the objectives of the study above, the author uses survey methods using test and measurement techniques. The population of this study was male students and female students of SMA Negeri 3 Ciamis Regency totaling 30 people consisting of 15 boys and 15 girls. The research instrument used to collect the data was the measurement of fat percentage using a skinfold tool. Based on data analysis using SPSS series 22, the results of data processing are as follows: 1. The lowest description of fat measurement data in men was 16.50 and the highest description of fat measurement data was 37.90. The lowest fat measurement data description in the princess was 19.20 and the highest fat measurement data description was 35.60.2. The normality data for the female is 0.938 > 0.05 and the normality data for the male is 0.729 > 0.05 meaning that the data for the male and female are normally distributed, 3. The body fat percentage value for the girls was 26.55% while the body fat percentage value for the boys was 26.01%. The results showed that the measurement of body fat percentage in male and female students of SMA Negeri 3 Ciamis Regency was included in the excess category of the norm, namely 15-20% of the normal category for boys and the norm of 20-25% of the normal category for girls.